Preoperative chemoradiation may be more effective for esophageal squamous cell carcinoma compared with adenocarcinoma: results from 15 randomized controlled trials of 2,250 patients - Ma, Wen-Juan; Zhang, Qiu-Ning; Shi, Shu-Zhen; Zhang, Xiao-Ying; Zhao, Ye; Tian, Jin-Hui; Wang, Xiao-Hu (Translational Cancer Research, 2018)
Background: Although preoperative chemoradiation (CRT) is considered a standard treatment for patients with esophageal cancer, the results obtained from a variety studies concerning this treatment type still do not completely concur. The purpose of this study is to evaluate the efficacy of preoperative CRT on different histological types in the treatment of esophageal cancer, and to clarify the benefits of preoperative CRT for esophageal cancer. Methods: PubMed, EMBASE, Web of science and Cochrane library were searched for eligible studies published up to December 2017. Three primary out-comes were analyzed. Pooled hazard ratio (HR) and 95% confidence intervals (95% CI) were calculated using a random effects or fixed effects. Heterogeneity of included studies was assessed using the I2 test. Publication bias was examined by the Begg’s funnel plot. Results: Fifteen RCTs totaling 2,250 patients were included, compared with surgery alone (SA), the HR (95% CI) for the overall survival (OS) was 0.88 (0.81–0.97), the disease-free survival (DFS) rate was 0.78 (0.64–0.96), and the progression-free survival (PFS) rate was 0.72 (0.56–0.91). To clarify the effect of histological differences on CRT, a subgroup analysis was performed, and the results showed that there was no statistically significant difference in the HR of the OS in squamous cell carcinoma (SCC) and adenocarcinoma (AC) for those treated with preoperative CRT compared with SA [HR of SCC =0.92 (0.83–1.01), P=0.085; HR of AC =0.77 (0.55–1.08), P=0.135]. There was however a statistically significant difference in the HR of the PFS in SCC and AC for those treated with preoperative CRT compared with SA [HR =0.48 (0.32–0.71) for SCC and =0.83 (0.57–1.21) for the AC]. The indirect compare results show there was no statistically significant difference between SCC and AC in OS, ROR (=1.19, 95% CI: 0.84–1.70), but have a statistically significant difference in PFS, ROR (=0.58, 95% CI: 0.33–1.00). Conclusions: Preoperative CRT can improve the OS, PFS and DFS of esophageal cancer. The results of subgroup analyses show that preoperative CRT can improve the PFS of esophageal SCC, but not esophageal AC. However, there was no significant difference in the OS of SCC and AC. And the indirect comparison results confirmed it.